Medical students’ perceptions of stress due to academic studies and its interrelationships with other domains of life: a qualitative study - Bergmann, Christin; Muth, Thomas; Loerbroks, Adrian (Medical education online, 2019)
Background: Medical students have been found to experience considerable stress due to their academic studies. The high demands associated with academic studies may interfere with demands in other domains of life. Conversely, demands in those other domains of life may conflict with academic studies.Objective: We aimed to better understand the potential inter-relationships between the demands related to academic studies and in other domains of life.Design: A total of 68 medical students from a medical school in Germany participate in eight focus groups. Sessions were structured by a topic guide and were recorded, transcribed and content-analyzed.Results: Embarking on one’s medical studies was perceived to be associated with important personal challenges, such as living alone for the first time and finding a new social role in one’s peer group. Permanent stress was perceived to result in emotional exhaustion, which spilled over in other domains of life. Students reported to feel guilty if they did not spend their limited spare time on learning. Consequently, they felt to have little time for leisure time activities and a healthy lifestyle. Feelings of social isolation, especially during exam phases, were reported. Leisure activities were perceived to facilitate recovery from academic stress. Social ties were subjectively able to reduce stress, but also to increase stress due to demands. Side jobs were perceived to increase stress and to be time-consuming and were thus perceived to result in poorer academic performance. Certain personality characteristics seemed to amplify those perceptions. For instance, high levels of conscientiousness were felt to relate to higher expectations regarding one’s academic performance and thus increased stress.Conclusion: The demands associated with medical studies, the demands in private life, lacking resources for recovery and certain personal traits as well as interactions between those domains can contribute to stress among medical students and reduce well-being.
Gesehen am 29.05.2019